2005
DOI: 10.1002/ird.187
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dripper clogging and filtering performance using municipal wastewater

Abstract: The paper discusses some drip irrigation system management problems according to the performance of emitters and filters shown in six trials conducted in Sicily (Italy) using six kinds of municipal wastewater that has not undergone previous advanced treatment. Nine types of filters (gravel media, disk and screen) and five types of drip emitters (vortex, labyrinth and long-path) were tested. The performance of the emitters and filters tested depends on the quality of the wastewater. Total suspended solids, BOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Soil microorganisms and nutrient conditions are influenced by pH value [25][26][27] and have to be considered as important parameter when microirrigation is used due to salts precipitation with consequent occlusion problems in the emitters and other components of the system [28,29]. Extreme pH values, especially influencing nutrients availability, affect crop growth and production [30][31][32][33].…”
Section: The Agronomic Quality Indicatorsmentioning
confidence: 99%
“…Soil microorganisms and nutrient conditions are influenced by pH value [25][26][27] and have to be considered as important parameter when microirrigation is used due to salts precipitation with consequent occlusion problems in the emitters and other components of the system [28,29]. Extreme pH values, especially influencing nutrients availability, affect crop growth and production [30][31][32][33].…”
Section: The Agronomic Quality Indicatorsmentioning
confidence: 99%
“…Emitter clogging is affected by many factors such as irrigation water quality (Capra & Scicolone, 2005), emitter type , geometric parameters of the flow path , and irrigation operation mode (Hills et al, 1989). For a drip irrigation system using saline water, Hills et al (1989) analysed the effect of different management schemes on emitter clogging, and found that nightonly irrigation and subsurface irrigation failed to prevent chemical precipitation; lowering of the pH of the water gave the least clogging.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the suspended particulate matter in the water is prone to physical flocculation with drip fertigation, which becomes a bridge between microbial growth and chemical adsorption. The composite clogging materials with higher stability will be formed by the catalysis effect of the microbes and salt ions, which results in emitter clogging (Capra and Scicolone, ; Gouider et al, ; Niu et al, ; Ahmed et al, ). Therefore, an investigation of water flow characteristics and sediment flocculation–deposition intensities and distribution patterns in the emitters was necessary.…”
Section: Introductionmentioning
confidence: 99%